Dynamical Substructures of Galactic Globular Clusters II. NGC 6934 - Jongwhan Rhee; Young-Jong Sohn; Min Shin; Aram Kang (Journal of Astronomy and Space Sciences, 2004)
The variations of the dynamical substructures of NGC 6934 have been investigated by means of performing point spread function stellar photometry and the surface photometry on BV CCD images of NGC 6934. Our results show that overall variations of ellipticity and position angle range in 0.02˜0.08 and -90° ˜ +90°, respectively out to three times the half light radius. The inner (reff < rh) substructures of NGC 6934 inferred from the variations of ellipticity and position angle are mainly affected by the bright red giant populations, while the effects of the other giant populations are weaker than those of the bright red giant populations. Horizontal branch populations and faint red giant star populations affect the dynamical substructures of NGC 6934 in the region of rh < reff < 3rh.